2008
DOI: 10.1021/jf803298z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Serotonergic Activity of Black Cohosh and Identification of Nω-Methylserotonin as a Potential Active Constituent

Abstract: Cimicifuga racemosa(L.) Nutt. (syn. Actaea racemosa L., black cohosh) is used to relieve menopausal hot flashes, although clinical studies have provided conflicting data, and the active constituent(s) and mechanism(s) of action remain unknown. Since serotonergic receptors and transporters are involved with thermoregulation, black cohosh and its phytoconstituents were evaluated for serotonergic activity using 5-HT7 receptor binding, cAMP induction, and serotonin selective reuptake inhibitor (SSRI) assays. Crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 47 publications
3
80
0
1
Order By: Relevance
“…14 With respect to serotonin, black cohosh has shown 5-HT7 receptor binding and activation in vitro. 57,58 The recently identified black cohosh compound, N-ω-methylserotonin, has been shown to bind the 5-HT7 receptor with strong affinity, induce cAMP as a second messenger, and block serotonin reuptake, suggesting serotonergic activity for black cohosh. 58 Burdette et al 50 found that black cohosh bound strongly to 3 receptor subtypes (5-HT 1A, 1D, and 7), thereby acting as a partial agonist.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 With respect to serotonin, black cohosh has shown 5-HT7 receptor binding and activation in vitro. 57,58 The recently identified black cohosh compound, N-ω-methylserotonin, has been shown to bind the 5-HT7 receptor with strong affinity, induce cAMP as a second messenger, and block serotonin reuptake, suggesting serotonergic activity for black cohosh. 58 Burdette et al 50 found that black cohosh bound strongly to 3 receptor subtypes (5-HT 1A, 1D, and 7), thereby acting as a partial agonist.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…57,58 The recently identified black cohosh compound, N-ω-methylserotonin, has been shown to bind the 5-HT7 receptor with strong affinity, induce cAMP as a second messenger, and block serotonin reuptake, suggesting serotonergic activity for black cohosh. 58 Burdette et al 50 found that black cohosh bound strongly to 3 receptor subtypes (5-HT 1A, 1D, and 7), thereby acting as a partial agonist. Since the 5-HT 1A and 7 receptor subtypes are present in the hypothalamus, it has been proposed that serotonergic activity in the hypothalamic thermoregulatory centers may be responsible for the reduction in hot flashes.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Recently, it has been demonstrated the presence of N-methylserotonin (a derivative of serotonin) and triterpenes (with GABA-ergic action) in various extracts of CR [23]: their synergistic action seems to improve the climacteric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of black cohosh, which apparently lacks estrogenic activity, as a natural alternative to Hormone Replacement Therapy led to a significant increase in its demand and, since 2008 it has been one of the top-ten selling herbal dietary supplement in the United States with total sales of more than $8 million [3]. Although a large number of secondary metabolites have been identified from roots and rhizomes, a mechanism for black cohosh containing extracts is unknown, and even controversial [1,4,5], with recent evidence suggesting a serotonergic mechanism of action [6].…”
Section: Introductionmentioning
confidence: 99%